Pengaruh NPL, LDR, NIM terhadap Profitabilitas di Masa Pandemi Covid-19 - Rizka Aufa Tiana; Nurhayati (UNISBA Press, 2022)
Abstract. The COVID-19 pandemic has had an impact on the health of living things. However, the COVID-19 pandemic has also had an impact on economic health, especially in the financial sector. This study aims to determine the effect of the Covid-19 pandemic on the profitability of commercial banks listed on the IDX using the Net Interest Margin (NIM), Loan to Deposit Ratio (LDR), Non Performing Loan (NPL) ratio. This research uses financial reports from 33 commercial banks in Indonesia during the Covid-19 pandemic in the 2019-2021 period. Secondary data obtained through the Indonesian Perbnkaan Statistics published by the Financial Services Authority and through the website www.idx.co.id the method used in this research is verifiable with quantitative shorthand using SPSS 18. The results of this study show that the Loan to Deposit Ratio, Non Performing Loan, has a significant negative impact on Profitability. According to the Net Interest Margin ratio, it has a significant positiv effect on Profitability. Abstrak. Pandemi covid-19 memberi dampak pada kesehatan makhluk hidup. Namun, pandemic covid-19 pun memberi dampak pada kesehatan ekonomi terutama pada sektor perbnkaan. Penelitian ini bertujuan untk mengatahui pengaruh pandemic covid-19 pada profitabilitas bank umum yang terdaftar di BEI dengan menggunakan rasio Net Interest Margin (NIM), Loan to Deposit Ratio (LDR), Non Performing Loan (NPL). Penelitin ini menggunakan laporn keuangan dari 33 bank umum di Indonesia selama pandemi covid-19 pada periode 2019-2021. Data sekunder diperoleh melalui Statistik Perbnkaan Indonesia yag dipublikasi Otoritas Jasa Keuangan dan melalui website www.idx.co.id metod yang digunakan dalam penelitn ini adalh verifikatif dengan pendektan kuantitatif meggunakan SPSS 18. Hasil penelitian ini menunjukkan bahwa Loan to Deposit Ratio, Non Performing Loan, berpengruh negatif signifikan teradap Profitabilitas. Sedngkan pada rasio Net Interest Margin berpengaruh positiv signifikan terhadap Profitabilitas.